BRAND IDENTITY ANALYSIS OF FACEBOOK META LOGO. INC. AND M-SENSE MIGRAINE USING SEMIOTICS AND VISUAL COGNITIVE - Varlina, Vivi; Noviandari, Auriza Cantika; Irnando, Hadrian (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2024)
Logo has a significant role in building brand identity. Nevertheless, the understanding of visual identity from one brand to another often experiences visual cognitive differences. This affects the identity of a brand due to a lack of knowledge of visual information such as the case of M-sense Migraine and Meta Facebook. In this study, researcher used the descriptive analysis as a method with semiotics and visual cogntive approach. The results explained that there is misinterpretation of visual information related to Meta logos and M-sense. The lack of knowledge of the audience towards both brands which ultimately creates confusion in the minds of the audience and undermines an exclusivity elements in building brand identity.